G protein pathways. - Iyengar, Ravi; Hildebrandt, John D. (Methods in enzymology, 2002)
This third volume in the trio covering G proteins, features integrated approaches to studying G proteins. Methods pertaining to signaling mechanisms are presented, including theoretical and modeling approaches, biochemistry and molecular biology, and cell biology and physiology. The techniques for studying the structure and function of G proteins are important not only to those with specific research interests in them, but also endocrinologists and pharmacologists conducting research on signaling mechanisms that are increasingly understood to interact with G proteins.